PHYSICAL FITNESS OF PHYSICAL EDUCATION STUDENTS OF AN UNIVERSITY OF RIO DE JANEIRO (Fiep Bulletin - online, 2012)
The association of physical fitness health related as a concept and an operational tool to measure a set of the physiological, psychological and physical that each individual has in his life story in a given moment, whose levels are closely linked to a reduced risk of developing hypokinetic nature. The present study aims to assess the fitness level undergraduate students in physical education from higher education institution Estacio de Sa University campus Akxe, located in Barra da Tijuca in the city of Rio de Janeiro. We evaluated 38 individuals, 10 women and 28 men with a mean age of 25 for women and 26 for men of the 3rd to 8th period.  Evaluations were performed functional with submaximal test. The values of submaximal Vo2 was as mean as much for women as for men classified as a fair result. We conclude through our research that most are rated with a good level of fitness, taking into account the results obtained through tests.
Keywords: Physical Fitness. Physical Education Students. Evaluation.